Changes in soil organic carbon stocks after conversion from forest to oil palm plantations in Malaysian Borneo. (27th September 2018) - Rahman, Niharika; de Neergaard, Andreas; Magid, Jakob; van de Ven, Gerrie W J; Giller, Ken E; Bruun, Thilde Bech
Abstract: The continuous rise in the global demand for palm oil has resulted in large-scale expansion of industrial oil palm plantations—largely at the expense of primary and secondary forests. The potentially negative environmental impacts of these conversions have given rise to closer scrutiny. However, empirical data on the effects of conversion of forests to industrial oil palm plantations on soil organic carbon (SOC) stocks is scarce and patchy. We evaluated the changes in SOC stocks after conversion of tropical forest into oil palm plantations over the first and second rotation period in Sarawak, Malaysian Borneo. Soil samples were collected from three age classes of oil palm plantations converted from forest (49, 39 and 29 years ago respectively) with three replicate sites and four adjacent primary forest sites as reference. In each site under oil palm, the three management zones, namely weeded circle (WC), frond stacks (FS), and between palm (BP), were sampled separately. All soil samples were collected from five soil layers (0–5, 5–15, 15–30, 30–50 and 50–70 cm). Samples were analysed for SOC concentration, soil bulk density, pH and soil texture. Results showed SOC stocks declined by 42%, 24% and 18% after 29, 39 and 49 years of conversion respectively. Significant differences in SOC stocks were found among different management zones in the oil palm plantations, and the trend was similar for all age classes: FS > WC > BP, demonstrating the necessity of considering within-plantation variability when assessing soil C stocks. The largest differences between SOC stocks of the reference forest and converted plantations were found in the topsoil (0–15 cm depth) but differences were also found in the subsoil (>30 cm). Our results will contribute towards future modelling and life cycle accounting to calculate the carbon debt from the conversion of forest to oil palm plantations.